2022
DOI: 10.3390/min12060711
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Insights Gained from a Field Deployment of Dithionite and Acetate at a Uranium In Situ Recovery Mine

Abstract: Mining uranium by in situ recovery (ISR) typically involves injecting an oxidant and a complexing agent to mobilize and extract uranium in a saturated ore zone. This strategy involves less infrastructure and invasive techniques than traditional mining, but ISR often results in persistently elevated concentrations of U and other contaminants of concern in groundwater after mining. These concentrations may remain elevated for an extended period without remediation. Here, we describe a field experiment at an ISR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Therefore, δ 34 S SO4 and δ 18 O SO4 in GC groundwater were both inherited from rainwater and modified by bacterial sulfate reduction. However, SO 4 2− reduction would be inhibited under strongly oxic conditions in production wells (Reimus et al., 2022), which limited the contribution of sulfate reduction to positive δ 34 S and δ 18 O in both M2 and M1. Lower δ 34 S SO4 and δ 18 O SO4 in production wells would be caused by pyrite oxidation in the aquifer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, δ 34 S SO4 and δ 18 O SO4 in GC groundwater were both inherited from rainwater and modified by bacterial sulfate reduction. However, SO 4 2− reduction would be inhibited under strongly oxic conditions in production wells (Reimus et al., 2022), which limited the contribution of sulfate reduction to positive δ 34 S and δ 18 O in both M2 and M1. Lower δ 34 S SO4 and δ 18 O SO4 in production wells would be caused by pyrite oxidation in the aquifer.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work has also shown that reductants downgradient from mining areas may help attenuate elevated U concentrations [142]. Ultimately, the success of restoration is subject to the geochemical constraints at each site combined with the choice of restoration techniques [143], which vary from site to site, and even possibly vary within different production areas at the same mines.…”
Section: Contamination Of Groundwater After Isr Mining (Pathway 4)mentioning
confidence: 99%
“…Although neutral in situ leaching (ISL) is an economically advantageous mining method for extracting low-grade sandstone uranium (U), , restoration of affected groundwaters to premining (baseline) water quality is subject to considerable uncertainty. U­(VI) can be removed from groundwater by sorption, precipitation, and reduction, which are expected to play an important role in U natural attenuation. Reduction of U­(VI) is preferred due to its long-term stability, which converts U­(VI) to U­(IV) and precipitates from solution. , Sandstone-hosted U deposits are commonly associated with reductants (e.g., pyrite and OM). Multiple electron donors (e.g., OM and pyrite) and biogeochemical processes (e.g., sulfate bioreduction) can promote U­(VI) reduction. , …”
Section: Introductionmentioning
confidence: 99%